Development of RANDAI-STEM Integrates Teaching Module to Enchance Scientific Communication Skills among Fase D Student - Melati Latifah; Fitri Arsih; Heffi Alberida; Elsa Yuniarti (Postgraduate, University of Mataram, 2025)
21st-century education demands that students not only master content but also possess scientific communication skills, thereby requiring innovative learning approaches to develop these competencies. The STEM approach, which integrates science, technology, engineering, and mathematics, along with the RANDAI learning model culturally-based and problem-solving oriented is considered effective in fostering such skills. This development research employed the Plomp model, consisting of three phases: preliminary research, prototyping, and assessment. The object of the study was a RANDAI Teaching Module integrated with STEM, with Grade VIII students as the subjects. The instruments used included tools for assessing validity, practicality, and effectiveness to measure students’ scientific communication and argumentation skills. Data analysis for validity and practicality employed descriptive analysis, while effectiveness was analyzed using ANOVA tests with SPSS software. The results showed that the module is valid with a score of 87.33%, highly practical with scores of 92.44% from teachers and 91.24% from students, and effective in enchance students' scientific communication skills